Agronomic traits and growing cattle performance for whole-plant corn and forage and grain sorghum silages - B.S. Dalke; R.N. Jr. Sonon; D.L. Holthaus; L. Pfaff; K.K. Bolsen; Matthew A. Young (Kansas Agricultural Experiment Station Research Reports, 1994)
Agronomic and cattle performance traits were measured for the following silages produced in 1992: irrigated Pioneer 3377 corn, ensiled with or without Biotal® silage inoculant; DeKalb 42Y grain sorghum; and Cargill 200F, Pioneer 947, DeKalb FS-5 and FS-25E, and Northrup King (NK) 300 forage sorghums. All sorghums were grown under dryland conditions. The irrigated corn had the highest whole-plant dry matter (DM) and grain yields, and NK 300 and DeKalb FS-5 had the highest whole-plant DM yields among the sorghums. NK 300 also had the highest grain yield among the sorghums; DeKalb FS-5 and FS-25E had the lowest. Steers fed the irrigated corn silages had the fastest and most efficient gains, and the late-season forage sorghum, DeKalb FS-25E, produced the slowest and least efficient gains. Inoculating the corn silage increased DM recovery, fermentation efficiency, and steer gain per ton of crop ensiled.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Silage; Corn; Sorghum; Growing cattle